(untitled) (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2022)
Tuberculosis is an epidemic infectious disease, so it is necessary to follow the guidelines issued by the World Health Organization, which is one of the goals of countries, and it is a disease that affects the respiratory system and the rest of the body. (2) As for the environment, the highest percentage was reached in the countryside (183) and urban (136) at the governorate level, while the percentage of males was higher than the percentage of females. Females prefer administrative work on the one hand, and spend a number of them at home, which reduces the injury. As for the level of academic achievement, the injuries in the primary stage reached the highest injury (150).